Coherence-based measurement of non-Markovian dynamics in an open quantum system - Yugra, Y.; De Zela, F.; Cuevas, Á. (American Physical Society, 2020)
We present a theoretical scheme and its experimental proof of principle for an open quantum system undergoing Markovian and non-Markovian evolutions. We exhibit these two regimes by diagnosing them with the relative entropy of coherence of two polarization qubits playing the roles of system and ancilla. These are initially prepared in a polarization maximally entangled state of a photon pair produced by spontaneous parametric down-conversion. We induce Markovian and non-Markovian regimes in the system's dynamics with the help of two auxiliary qubits, experimentally implemented by optical paths in a layout of Sagnac and Mach-Zehnder interferometers. We replicate system-environment interactions by means of an amplitude damping channel and a suitably designed inversion of it. In our scheme, one needs only two experimentally accessible parameters to achieve Markovian and non-Markovian regimes.
Keywords: Physics; Coherence (philosophical gambling strategy); Qubit; Markov process; Statistical physics; Quantum mechanics; Quantum; Photon; Open system (computing); Computer science; Mathematics; https://purl.org/pe-repo/ocde/ford#1.03.03